Desa Cibinong sebagai desa percontohan budi daya ikan hias dimasa pandemi Covid-19 - Fathimah, Nur Sabrina; Maulidah, Inas Nabilatul; ., Jumeri; Hamidah, Anis; Safitri, Wiena (e-Journal BUDIDAYA PERAIRAN, 2022)
The aim of this study is to explore the methods, strategies, and other aspects of cultivation activites in Cibinong Village that potentially lead this village to become pilot village for ornamental fish cultivation during the COVID-19 pandemic. This study use qualitative method through interviews, observations, and documentation. The availability of land  to  make  ponds  in  almost  every  resident’s  house,  abundant  water  supply,  strategic position  that  close  to  the  center  of  ornamental  fish  market,  and  willingness  to  share experience between resident are important aspects that make this village become successful in cultivation of ornamental fish. After analyzing and exploring it can  be concluded that Cibinong Village in Gunung Sindur District can become one of the pilot villages for ornamental fish cultivation during the COVID-19 pandemic.